The multiple roles of fatty acid handling proteins in brain - Moullé, Valentine S.; Cansell, Céline; Luquet, Serge; Cruciani-Guglielmacci, Céline (Frontiers in Physiology, 2012)
Lipids are essential components of a living organism as energy source but also as constituent of the membrane lipid bilayer. In addition fatty acid (FA) derivatives interact with many signaling pathways. FAs have amphipathic properties and therefore require being associated to protein for both transport and intracellular trafficking. Here we will focus on several fatty acid handling proteins, among which the fatty acid translocase/CD36 (FAT/CD36), members of fatty acid transport proteins (FATPs), and lipid chaperones fatty acid-binding proteins (FABPs). A decade of extensive studies has helped decipher the mechanism of action of these proteins in peripheral tissue with high lipid metabolism. However, considerably less information is available regarding their role in the brain, despite the high lipid content of this tissue. This review will primarily focus on the recent studies that have highlighted the crucial role of lipid handling proteins in brain FA transport, neuronal differentiation and development, cognitive processes and brain diseases. Finally a special focus will be made on the recent studies that have revealed the role of FAT/CD36 in brain lipid sensing and nervous control of energy balance.